2000
DOI: 10.1159/000051966
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis Predicts Poor Prognosis in Gastric Carcinoma

Abstract: Background/Aims: New prognostic factors in gastric carcinoma to determine the prognosis of the disease or to identify patients who will benefit from adjuvant therapy are being researched. The aim of this study is to investigate the correlation between microvessel count (MVC) and various clinicopathologic features in gastric carcinoma in order to evaluate the role of angiogenesis on the prognosis of gastric cancer. Methods: Fifty-seven patients who underwent surgical intervention for gastric carcinoma between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
9

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
1
4
0
9
Order By: Relevance
“…Several investigators have reported that there was a close correlation between small vessel counts and liver metastasis in the colorectum and other organs. [18][19][20][21] Accordingly, we speculate that carcinoma cells traveled to the liver via proliferated small vessels.…”
Section: Discussionmentioning
confidence: 92%
“…Several investigators have reported that there was a close correlation between small vessel counts and liver metastasis in the colorectum and other organs. [18][19][20][21] Accordingly, we speculate that carcinoma cells traveled to the liver via proliferated small vessels.…”
Section: Discussionmentioning
confidence: 92%
“…Erenoglu et al [10]reported that microvessel count may be a valuable prognostic factor to predict patients at high risk for possible recurrences. Histologic type as a prognostic factor is still controversial [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…No estudo da angiogênese com Fator VIII, Erenoglu et al 6 , não encontraram correlação entre densidade microvascular e idade ou sexo dos pacientes no câncer gástrico. Dos marcadores que analisam a evolução do câncer gástrico os que representam a proliferação celular 8 e a angiogênese 19 parecem ser os melhores.…”
Section: Discussionunclassified
“…O estudo realizado por Erenoglu et al 6 em 57 pacientes com câncer gástrico encontrou correlação entre densidade microvascular e parâmetros como tipo difuso e indiferenciado, invasão de serosa e linfonodal, estadio avançado e metástase distal, nos quais se apresentaram com maior densidade vascular e maiores índices, afetando a sobrevida adversamente. Os autores concluiram que a densidade microvascular no carcinoma gástrico pode ser fator prognóstico valioso para predizer pacientes com alto risco para recorrência e para decidir terapia adjuvante pós-operatória.…”
Section: Discussionunclassified